Menanamkan Motivasi Belajar Online dari Orang Tua melalui Seminar Parenting - Amen Natanael Togatorop; Anggy Giri Prawiyogi; Andes Safarandes Asmara (Jurnal Sekolah Dasar, 2023)
Since being shocked by the corona virus / Covid-19. This virus has spread widely to various parts of the world including Indonesia. Until April, the Indonesian government announced a lockdown policy, namely completing all activities, which carried out settlements in worship activities, schools, offices, or universal facilities, social and cultural activities, modes of transportation, and other activities related to regional security, some of the mandatory requirements followed by regions following lockdown regulations. Courageous learning does not always go as desired, the problems faced by children are difficulty concentrating on learning and many school assignments. This can also cause a feeling of stress, boredom, and has the potential to cause depression in children, on the part of parents also have difficulties in accompanying their children to study at home, due to other responsibilities and difficulties understanding children's lessons and methods, also not understanding applications or features. which is used as a support for the brave learning process. However, in this regard, especially in Pangulah Utara Village, Kota Baru District, Karawang, where generally parents are not highly educated, there are certainly difficulties in this regard. These various obstacles need confirmation between teachers, students, as well as the cooperation between parents and children and parents and good teachers so that the learning process carried out at home can run as expected.